2017
DOI: 10.1073/pnas.1709075114
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical enhancement of chemoreceptor detection sensitivity by a sensory adaptation enzyme

Abstract: A sensory adaptation system that tunes chemoreceptor sensitivity enables motile Escherichia coli cells to track chemical gradients with high sensitivity over a wide dynamic range. Sensory adaptation involves feedback control of covalent receptor modifications by two enzymes: CheR, a methyltransferase, and CheB, a methylesterase. This study describes a CheR function that opposes the signaling consequences of its catalytic activity. In the presence of CheR, a variety of mutant serine chemoreceptors displayed up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…We detected two differentially migrating species of PilJ during liquid and surface growth (Suppl Fig 3A). By analogy to the migration of E. coli MCPs in methylation immunoblots 4045 , the slower migrating band is predicted to represent the unmethylated PilJ state, and the faster migrating band is predicted to represent a methylated form of PilJ (which we validate below). By calculating the fraction of methylated PilJ, we demonstrated that methylated PilJ was significantly increased after 2 h of surface growth compared to liquid growth (p=0.002; Fig 1D), suggesting that PilJ methylation increases in response to mechanical stimuli generated during surface contact.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…We detected two differentially migrating species of PilJ during liquid and surface growth (Suppl Fig 3A). By analogy to the migration of E. coli MCPs in methylation immunoblots 4045 , the slower migrating band is predicted to represent the unmethylated PilJ state, and the faster migrating band is predicted to represent a methylated form of PilJ (which we validate below). By calculating the fraction of methylated PilJ, we demonstrated that methylated PilJ was significantly increased after 2 h of surface growth compared to liquid growth (p=0.002; Fig 1D), suggesting that PilJ methylation increases in response to mechanical stimuli generated during surface contact.…”
Section: Resultsmentioning
confidence: 74%
“…In ∆chpB, the faster-migrating 3xFlag-PilJ band was the most abundant species, likely corresponding to methylated PilJ, with a corresponding increase in the fraction of methylated PilJ. Thus, like the migration behavior of E. coli MCPs [40][41][42][43][44][45] , methylated PilJ migrates faster than unmethylated PilJ in this experimental setup.…”
Section: Pilj Methylation Increases In Response To Mechanosensing And...mentioning
confidence: 84%
See 2 more Smart Citations
“…Much evidence indicates that methylation modulates the packing stability of the cytoplasmic methylation helix (MH) bundles in MCPs (Parkinson, 2010; Lai et al ., 2017). The predicted secondary structure of WspA is shown in Fig.…”
Section: Discussionmentioning
confidence: 99%